SOCIAL SKILL TRAINING PADA PENYANDANG SKIZOFRENIA - Dundu, Anita E. (UNIVERSITAS SAM RATULANGI, 2010)
Abstract: Besides psychotic symptoms, schizophrenic patients also show alterations in cognitive function, verbal information, and emotional response, due to disturbances of interpersonal interaction. The impact of all of these is the disturbance in social function. Treatment of schizophrenic patients with psychopharmacotherapy can only suppress the symptoms, but it can not overcome the functional deficit. For this reason, combination of psychopharmacotherapy, psychotherapy, and social rehabilitationin is introduced to obtain a better result in schizophrenic management. Social skill training is a part of the social rehabilitation that is very useful in improving the patientsâ€™ quality of life in preparing them to be functional in their society. Key words: schizophrenia, social rehabilitation, social skill training.Â Abstrak: Pada penyandang skizofrenia selain gejala-gejala psikotik juga terdapat perubahan dalam fungsi kognisi, informasi verbal dan respon emosi akibat terganggunya interaksi interpersonal, yang berdampak gangguan dalam fungsi sosial. Pengobatan skizofrenia dengan menggunakan psikofarmaka hanya dapat menekan gejala-gejala penyakit ini tetapi tidak dapat mengatasi defisit fungsional. Untuk hal ini, pada pengobatan skizofrenia terkini digunakan kombinasi psikofarmaka, psikoterapi dan rehabilitasi sosial. Social skill training merupakan salah satu bagian dari rehabilitasi sosial yang bermanfaat meningkatkan kwalitas hidup dalam mempersiapkan penyandang skizofrenia Â untuk dapat berfungsi kembali dalam masyarakat. Kata kunci: skizofrenia, rehabilitasi sosial, social skill training.